Finite element simulation of effect of residual stresses during orthogonal machining using ALE approach. (1st January 2013) - Krishnakumar, P.; Marimuthu, K. Prakash; Rameshkumar, K.; Ramachandran, K.I.
In this paper, a finite element model has been developed to predict the effect of residual stress induced in the work material during multiple pass turning of AISI 4340 steel. Chip morphology and force variation during machining are also quantified using the FE model. Finite element model was developed using arbitrary Lagrangian-Eulerian formulation along with Johnson-Cook material model and Johnson-Cook damage model. The finite element model developed in this study was validated experimentally by studying the chip morphologogy and cutting force variation during the machining. Results indicate that there is good correlation existing between numerical results and experimental results.